Analisis Potensi Kebangkrutan Perusahaan Sub Sektor Transportasi yang Terdaftar di BEI Sebelum dan Selama Pandemi Covid-19 - Viky Agustian; Rita Syofyan (Jurnal Ecogen, 2022)
The PSBB policy implemented by the government to deal with the COVID-19 pandemic resulted in a decline in company performance in the transportation sub-sector, resulting in a very drastic decrease in profits during the COVID-19 pandemic. This situation will make it difficult for the company to experience financial distress and even bankruptcy. This study objective is to analyze the bankruptcy of transportation companies listed on the IDX before and during the COVID-19 pandemic. The sample used in this study consisted of 40 companies listed on the Stock Exchange with a purposive sampling method. Annual financial report data is obtained from the Indonesia Stock Exchange. The data analysis technique used is the Altman Z-Score analysis using the third model formula for non-manufacturing companies. Based on this research, it can be concluded that there is a significant difference between the potential of bankruptcy of the transportation sub-sector companies before and during the covid-19 pandemic, this is proven by the Wilcoxon test results show a probability value < 0.05 or 0.043 < 0.05. Transportation sub-sector companies have the potential to go bankrupt during the covid-19 pandemic, this is proven by the average Z-Score of transportation companies which has decreased from -0.3458 to -1.2840 during the covid-19 pandemic. Keyword: altman z-score, bankruptcy analysis, transportation